2016
DOI: 10.5204/jld.v9i1.227
|View full text |Cite
|
Sign up to set email alerts
|

Bad Attitudes: why design students dislike teamwork

Abstract: <p>Positive experiences of teamwork in design contexts significantly improve students’ satisfaction with teaching and their attitudes towards future teamwork. Thus, an understanding of the factors leading to negative and positive team experiences can inform strategies to support effective teamwork. This paper examines design students’ perceptions and experiences of teamwork. Three sources of qualitative data were analysed: a pilot survey completed by 198 design students in four institutions; five focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 44 publications
1
32
0
3
Order By: Relevance
“…In addition, Tucker and Abbasi (2016) in their study show that students prefer to work individually because of their negative teamwork learning experiences. Among the factors accounting for the negative teamwork learning experiences are the unequal workload contribution, poor engagement in group meetings and also the poor quality of work contributed (Tucker & Abbasi, 2016). Additionally, the dependence of a student when they first look at the work of another partner prior starting their design studio projects also influences the emotions and readiness of the student to carry out their tasks (Ibrahim, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Tucker and Abbasi (2016) in their study show that students prefer to work individually because of their negative teamwork learning experiences. Among the factors accounting for the negative teamwork learning experiences are the unequal workload contribution, poor engagement in group meetings and also the poor quality of work contributed (Tucker & Abbasi, 2016). Additionally, the dependence of a student when they first look at the work of another partner prior starting their design studio projects also influences the emotions and readiness of the student to carry out their tasks (Ibrahim, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Tucker et al (20) stated that the learners' attitude toward teamwork creates a better learning environment. In spite of this issue, a positive approach towards teamwork among medical students was very low.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the average of three factors, i.e. attitude toward teamwork efficiency (6.13), attitude toward teamwork (5.4), and attitude toward physician's role in teamwork (5.35), the minimum average belonged to the attitude towards physician's role (20). Henderson (2012) believed that experts were concerned about losing their autonomy/ independency during the work/task.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing body of literature aimed at enhancing group work experience and outcomes has emerged (Tucker & Abbasi, 2016). Espey (2010) found that attitudes to group work can change (even throughout a semester); other studies have shown that those who enjoyed group work had relationships built on trust, familiarity, and commitment to producing quality work and team cohesion (Ku, Tseng, & Akarasriworn, 2013; Tseng & Yeh, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%